2022
DOI: 10.1093/schbul/sbac002
|View full text |Cite
|
Sign up to set email alerts
|

Dimensions of Formal Thought Disorder and Their Relation to Gray- and White Matter Brain Structure in Affective and Psychotic Disorders

Abstract: Factorial dimensions and neurobiological underpinnings of formal thought disorders (FTD) have been extensively investigated in schizophrenia spectrum disorders (SSD). However, FTD are also highly prevalent in other disorders. Still, there is a lack of knowledge about transdiagnostic, structural brain correlates of FTD. In N = 1071 patients suffering from DSM-IV major depressive disorder, bipolar disorder, or SSD, we calculated a psychopathological factor model of FTD based on the SAPS and SANS scales. We teste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 72 publications
0
27
0
Order By: Relevance
“…This multilingual corpus may represent an ideal benchmark dataset for testing the reliability and generalizability (e.g., out of sample predictability) of voice analysis results in schizophrenia 73 , and the necessary ground for assessing its clinical applicability 74 . Not least, future studies should focus more on cross-diagnostic comparisons aimed at capturing symptom dimensions which extend over a single disorder 75,76 , and implement longitudinal designs able to test more complex hypothesis on the interaction between antipsychotic medication type and dosage, clinical (e.g., illness severity and duration) and sociodemographic (e.g., sex differences 77 ) characteristics, and speech production.…”
Section: Discussionmentioning
confidence: 99%
“…This multilingual corpus may represent an ideal benchmark dataset for testing the reliability and generalizability (e.g., out of sample predictability) of voice analysis results in schizophrenia 73 , and the necessary ground for assessing its clinical applicability 74 . Not least, future studies should focus more on cross-diagnostic comparisons aimed at capturing symptom dimensions which extend over a single disorder 75,76 , and implement longitudinal designs able to test more complex hypothesis on the interaction between antipsychotic medication type and dosage, clinical (e.g., illness severity and duration) and sociodemographic (e.g., sex differences 77 ) characteristics, and speech production.…”
Section: Discussionmentioning
confidence: 99%
“…37 Overall, our model is very similar to the 3-factor model for formal thought disorder reported by Stein et al in their crossdiagnostic sample of N=1,071. 25 They describe an emptiness factor (poverty of speech and content, increased latency, and blocking), a disorganization factor (tangentiality, circumstantiality, derailment, pressure of speech), and an incoherence factor (incoherence, distractibility). The principal differences are that we include decreased vocal inflection in our impaired expressivity factor (since we are looking at speech as a whole, and not specifically thought disorder), and that we prefer the term "inefficiency" over "disorganization" because "disorganization" is an overly broad term than can The 3-factor model proposed here can be understood in the context of linguistic theories on pragmatics.…”
Section: Discussionmentioning
confidence: 99%
“…We need to define cross-diagnostically diagnoses. 25 Speech graph features have been shown to be a good marker of thought disorder in mania and SSD, 15 and to be related to cross-diagnostic psychopathological dimensions. 26 referential: echolalia and self-reference).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two large transdiagnostic symptom mapping studies of FTD have been reported in recent times, drawing on the same FOR2107 cohort of n=1071 patients [49]. In whole-brain exploratory analyses relating gray matter volume and white matter integrity to positive FTD (derived from a multi-scale factor analysis) and FTD-scale specific positive (disorganisation, incoherence) and negative FTD factors (emptiness), Stein and colleagues report associations outside of the core LN (right middle frontal gyrus, left middle occipital gyrus, anterior thalamic radiation and right posterior cingulum) [50,51]. Conventional language regions do not appear prominent in these transdiagnostic analyses even when a focussed ROI analysis is attempted [51].…”
Section: Specificity Of Ln Dysfunction To Ftdmentioning
confidence: 99%